(untitled) (Forum Penelitian Agro Ekonomi, 2023)
Indonesia could not meet its soybean demand over the last three decades, so it still depends on imports. This study aims to analyse the performance of production, consumption, financial feasibility, and competitiveness of domestic soybeans that affect the achievement of self-sufficiency. This study is a literature review that examines data and information from various sources. The results showed that (1) soybean farming is less profitable, (2) soybean farming has no competitiveness compared to other crops, and (3) soybean also has no competitiveness in all trade regimes. The ratio of soybean prices to rice prices continues to decline. The self-sufficiency analysis also shows a declining figure. These weaknesses have caused Indonesia’s soybean area and production sharply declined. Soybean self-sufficiency programs in Indonesia can only be realistic and achieved with a significant breakthrough. Indonesia must grow soybeans in large areas by developing soybean production centers or belts. Providing land devoted to soybeans and assigning state-owned and private companies to carry out large-scale soybean farming is necessary. Without this breakthrough, Indonesia’s journey towards self-sufficiency in soybean will be unrealistic, remain longer and not reach its goal.